Ethics and nutrition safety in patient care during COVID-19 pandemic - Dian Permatasari (Indonesian Nutrition Association, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has impacted all aspects of our population. Ethical dilemmas related to the care of patients in the COVID-19 pandemic need to be rapidly addressed by multidisciplinary bioethics committees, with the development of policies and procedures to assist providers in making difficult allocation decisions. Recent ethical considerations regarding allocation of scarce resources, such as mechanical ventilators, have been proposed. These can apply to other disciplines such as nutrition support, although decisions regarding nutrition support have a diminished potential for devastating outcomes. The nutrition support professionals are pivotal in assessing the patient’s overall condition and need for, if any, nutrition interventions.